Land Covers Change Assessment After Small Dam’s Construction Based on the Satellite Data - Nabi Bux Bhatti; Altaf Ali Siyal; Abdul Latif Qureshi; Imtiaz Ali Bhatti (Salehan Institute of Higher Education, 2019)
The small dams were constructed in the study area for storing the rainwater. The present study was conducted to assess the impact of small dams on the LCC (Land Cover Change) in Nangarparkar, Pakistan based on the satellite data. The ENVI (Environment for Visualizing Images) software was used for classification of the four year’s images and three classes viz. water, vegetation, and soil were taken for detection of LCC. The MLH (Maximum Likelihood) supervised method was used to classify the multispectral satellite images. The classified results of the classes were found different each year before and after dam construction. Average results of the two years before dam’s construction revealed that water availability, vegetation cover and soil cover was 3.02%, 18.52%, and 32.30% respectively. However, after the dam construction, the water availability, vegetation cover and soil cover was 8.49%, 34.33%, and 17.15% respectively. Overall results revealed that water availability and vegetation cover were increased by 5.47 % and 15.18% respectively while soil cover decreased 15.15% after the construction of dams. Hence, based on the results, it is confirmed that the constructions of small dams have a direct and indirect positive impact on the land cover changes and it can play an important role in the resettlement of the communities of the arid areas.